Influence of ground shaking on the fault: numerical simulation - Nemirovich-Danchenko, M. M. (Journal of Physics: Conference Series)
The paper considers a possible model of the behavior of faults under the influence of external influences. A complication in the form of a step is assumed in the structure of the fault banks. A hook on a step leads to the appearance of two local stress concentration regions. A possible mechanism for slowing down the response to external stimuli is discussed. An external influence can be a shaking of the ground from a neighboring earthquake or a deformation tidal wave. The calculation is carried out within the framework of the elastic-brittle medium model by the finite-difference method supplemented with the ability to calculate cracks with the definition of their faces as free surfaces. As a result of the simulation, the emergence of a region of stress concentration is observed, which may not immediately lead to destruction. There will be an accumulation of damage as a result of a hook on the fault step, and the reaction to external influence will slow down. Over time, the medium exhausts the possibilities for implementing all the mechanisms of accommodation to the load, which leads to a break in the vicinity of the roughness with the emission of the next portion of seismic waves.